Isolation, Functional Characterization and Transmissibility of p3PS10, a Multidrug Resistance Plasmid of the Fish Pathogen Piscirickettsia salmonis - Saavedra, José; Grandón, Maritza; Villalobos-González, Juan; Bohle, Harry; Bustos, Patricio; Mancilla, Marcos (Frontiers in Microbiology, 2018)
Antibiotic resistance is a major public health concern due to its association with the loss of efficacy of antimicrobial therapies. Horizontal transfer events may play a significant role in the dissemination of resistant bacterial phenotypes, being mobilizable plasmids a well-known mechanism. In this study, we aimed to gain insights into the genetics underlying the development of antibiotic resistance by Piscirickettsia salmonis isolates, a bacterial fish pathogen and causative agent of salmonid piscirickettsiosis, and the main target of antibiotics used in Chilean salmon farming. We provide experimental evidence that the plasmid p3PS10, which harbors multidrug resistance genes for chloramphenicol (cat2), tetracyclines (tet(31)), aminoglycosides (sat1 and aadA1), and sulfonamides (sul2), is carried by a group of P. salmonis isolates exhibiting a markedly reduced susceptibility to oxytetracycline in vitro (128-256 µg/mL of minimal inhibitory concentration, MIC). Antibiotic susceptibility analysis extended to those antibiotics showed that MIC of chloramphenicol, streptomycin, and sulfamethoxazole/trimethoprim were high, but the MIC of florfenicol remained at the wild-type level. By means of molecular cloning, we demonstrate that those genes encoding putative resistance markers are indeed functional. Interestingly, mating assays clearly show that p3PS10 is able to be transferred into and replicate in different hosts, thereby conferring phenotypes similar to those found in the original host. According to epidemiological data, this strain is distributed across aquaculture settings in southern Chile and is likely to be responsible for oxytetracycline treatment failures. This work demonstrates that P. salmonis is more versatile than it was thought, capable of horizontally transferring DNA, and probably playing a role as a vector of resistance traits among the seawater bacterial population. However, the low transmission frequency of p3PS10 suggests a negligible chance of resistance markers being spread to human pathogens.